Fenomena Pajak dan Strategi Bertahan Bisnis Sektor Ritel dan Perdagangan di Tengah Perlambatan Ekonomi Indonesia Tahun 2026 - Shela Juni Rahmawati; Agus Rafli Sugianto; Bela Bela (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This study aims to analyze the phenomenon of tax burden, tax compliance, and tax-saving strategies and their influence on business survival strategies in Indonesia’s retail and trade sector amid the economic slowdown in 2026. Indonesia’s economic growth declined to 4.2% in the first quarter of 2026 from 5.1% in the previous year, creating considerable pressure on business sustainability, particularly in the retail and trade sector. This research employed a quantitative approach using a survey method involving 120 retail and trade business owners located in Jakarta, West Java, and Banten. Respondents were selected through purposive sampling. Data were collected using a structured questionnaire that met validity and reliability requirements and were analyzed using multiple linear regression with SPSS version 26 after fulfilling the classical assumption tests. The results indicate that tax burden (B = 0.287; p < 0.001), tax compliance (B = 0.341; p < 0.001), and tax-saving strategies (B = 0.398; p < 0.001) each have a positive and significant effect on business survival strategies, both individually and simultaneously. The F-test (F = 62.847; p < 0.001) confirms the overall significance of the regression model, while the coefficient of determination (R² = 0.621) shows that the three independent variables explain 62.1% of the variance in business survival strategies. These findings suggest that effective tax management, combined with the lawful utilization of tax incentives, plays a crucial role in strengthening business resilience and ensuring the sustainability of retail and trade businesses during periods of economic uncertainty.